Content adaptation procedures to cater for students with diverse academic backgrounds in deliveringTextile, Clothing and Design programmes in Zimbabwe. A case study of two universities of technology - Chimbindi, Felisia; Rembe, S. (International Journal of Scientific Research and Management (IJSRM), 2018)
Universities of technology in Zimbabwe enrol students with various background educational qualifications for Textile, Clothing and Design programmes. The students are combined and learn in same class resulting in high students’ failure rate, drop outs, late completion of degree programmes, and poor performance of graduates. Thus researchers sought to examine curriculum adaptation procedures used to cater for the students. Post-positivism paradigm in mixed method research approach was adopted for the study. Interviews with TCD management, document analysis, and questionnaire with lecturers yielded qualitative and quantitative data. Findings revealed that lecturers employed various uncoordinated methods to adapt the curriculum content to cater for the students